The Impact of Ratings and Influencer Marketing on Consumer Purchase Decisions For Skincare Products on The Shopee Marketplace - Selmadea Oktaviana; Dewi Shanti Nugrahani; Hesti Respatiningsih (International Journal of Economics, Commerce, and Management, 2025)
This study aims to examine the influence of ratings and influencer marketing on purchasing decisions for skincare products on the Shopee marketplace. This quantitative study involved 96 respondents and used multiple linear regression data analysis. The results show that ratings and influencer marketing have a significant influence. Purchasing decisions are influenced by ratings, which is the most dominant variable, meaning that the higher the rating, the greater the interest in the product. These findings emphasize the importance for sellers to maintain product and service quality to maintain high ratings and to collaborate with credible influencer marketers to strengthen their marketing strategies.